2019
DOI: 10.1111/dmcn.14426
|View full text |Cite
|
Sign up to set email alerts
|

Tatton‐Brown‐Rahman syndrome: cognitive and behavioural phenotypes

Abstract: The aim of this case series was to assess and characterise cognitive abilities, autistic traits and adaptive behaviour in Tatton-Brown-Rahman syndrome. The sample included 18 individuals with a clinical and genetic diagnosis of TBRS (11 males, seven females; mean age 17y 7mo, SD 9y 5mo, range 7y 2mo-33y 10mo). The British Ability Scales, Third Edition and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 14 publications
2
16
0
4
Order By: Relevance
“…Another example for the relevance of DNMTs in brain development and NDDs is the Tatton-Brown-Rahman syndrome (TBRS), a rare neurodevelopmental congenital anomaly syndrome that manifests with overgrowth, macrocephaly, and characteristic facial features, sometimes accompanied by autism spectrum disorder ( Figure 1 and Table 1 ; Yokoi et al, 2020 ). Patients with TBRS are characterized by mutations in DNMT3A , leading to different variants of this methyltransferase ( Lane et al, 2020 ). However, underlying connections to the observed cortical anomalies like cerebral overgrowth or metabolite accumulations in the prefrontal cortex in TBRS patients remain largely unclear so far ( Tenorio et al, 2020 ; Yokoi et al, 2020 ).…”
Section: Implications Of Epigenetic Mechanisms In Neurodevelopmental Diseasesmentioning
confidence: 99%
“…Another example for the relevance of DNMTs in brain development and NDDs is the Tatton-Brown-Rahman syndrome (TBRS), a rare neurodevelopmental congenital anomaly syndrome that manifests with overgrowth, macrocephaly, and characteristic facial features, sometimes accompanied by autism spectrum disorder ( Figure 1 and Table 1 ; Yokoi et al, 2020 ). Patients with TBRS are characterized by mutations in DNMT3A , leading to different variants of this methyltransferase ( Lane et al, 2020 ). However, underlying connections to the observed cortical anomalies like cerebral overgrowth or metabolite accumulations in the prefrontal cortex in TBRS patients remain largely unclear so far ( Tenorio et al, 2020 ; Yokoi et al, 2020 ).…”
Section: Implications Of Epigenetic Mechanisms In Neurodevelopmental Diseasesmentioning
confidence: 99%
“…El paciente de este artículo presenta un fenotipo compatible con STBR con sobrecrecimiento presente desde la etapa neonatal acompañado de trastornos del neurodesarrollo (tabla 1). La DI en los individuos con STBR varía desde individuos con capacidad limítrofe a DI severa, frecuentemente acompañada de TEA cuya severidad suele disminuir con la edad 7,16 .…”
Section: Discussionunclassified
“…El sobrecrecimiento y discapacidad intelectual (DI) son las características encontradas con mayor frecuencia en el STBR reportadas en > 80% de los casos, y su diagnóstico se basa en la presencia de estos dos rasgos y de una variante germinal en DNMT3A 7,8 . Otros hallazgos presentes en el 20%-80% de los individuos son una apariencia facial distintiva que evoluciona en el tiempo haciéndose aparente en la adolescencia con cejas bajas, prominentes y horizontales; incisivos centrales prominentes, hipermovilidad articular, obesidad, hipotonía, alteraciones psiquiátricas y del comportamiento, cifoescoliosis y convulsiones no febriles 8 .…”
Section: Introductionunclassified
“…Developments in neurosciences have shown that neither learning nor adaptive functioning is a fixed state. Hence it is unsurprising to note that all the adults scored in the non‐spectrum range on ADOS‐2 . In my opinion, such expression and/or evidence of neuroplasticity should prompt us to do the following.…”
mentioning
confidence: 98%
“…Hence it is unsurprising to note that all the adults scored in the non-spectrum range on ADOS-2. 1 In my opinion, such expression and/or evidence of neuroplasticity should prompt us to do the following. First, to give hope to patients and their carers.…”
mentioning
confidence: 99%